Spatially Resolved Kinetic Model of Parahydrogen Induced Polarisation (PHIP) in a Microfluidic Chip. Issue 19 (31st August 2021) - Ostrowska, Sylwia J; Rana, Aabidah; Utz, Marcel
Abstract: We report a spatially resolved kinetic finite element model of parahydrogen‐induced polarisation (PHIP) in a microfluidic chip that was calibrated using on‐chip and off‐chip NMR data. NMR spectroscopy has great potential as a read‐out technique for lab‐on‐a‐chip (LoC) devices, but is often limited by sensitivity. By integrating PHIP with a LoC device, a continuous stream of hyperpolarised material can be produced, and mass sensitivities of pmol s have been achieved. However, the yield and polarisation levels have so far been quite low, and can still be optimised. To facilitate this, a kinetic model of the reaction has been developed, and its rate constants have been calibrated using macroscopic kinetic measurements. The kinetic model was then coupled with a finite element model of the microfluidic chip. The model predicts the concentration of species involved in the reaction as a function of flow rate and position in the device. The results are in quantitative agreement with published experimental data. Abstract : We report a spatially resolved kinetic finite element model of parahydrogen‐induced polarisation in a microfluidic chip that was calibrated using on‐chip and off‐chip NMR data. The model predicts the concentration of species involved in the reaction as a function of flow rate and position in the device.